What's happening in cyber space?: An interdisciplinary approach - (:unkn) unknown (Peter Lang Publishing Group, 2020)
The term "cyberspace" that entered into our lives towards the end of the 20th century is defined as: "a global platform that consists of the network containing the infrastructures of information technologies with Internet, communication networks, computer systems, embedded processors and controllers". When this term is analysed, it is seen that nearly all informatics systems minimize the human control and at many platforms, they are connected to each other. Although the term "cyberspace" is very new, it is like a living organism that is coordinated with scientific disciplines such as finance, defence, health, education, transportation and security, in all manned and unmanned areas. Our interaction with this organism covers almost all our lifespan. When looked closer, it is seen that cyberspace must be researched not only from technology side but also from sociology and psychology sides. So, welcome to the cyberspace journey that we prepared for you in our book What's Happening in Cyberspace?. © Peter Lang GmbH Internationaler Verlag der Wissenschaften Berlin 2020. All rights reserved.